Methods & theories of art history - D'Alleva, Anne (London Laurence King Pub., 2005)
"Anne D'Alleva presents art history students with a clear and accessible introduction to the critical theories behind art historical practice. In outlining some of the most current and widely used theoretical perspectives, she helps the reader to understand the ideas that have shaped art history over the centuries."--BOOK JACKET.
Includes bibliographical references and index.
Keywords: Art -- History -- Methodology; Art -- Philosophy; Art criticism; Art -- Historiography -- Methodology